Advancements in Nanotechnology: Implications for Physics and Engineering - Ali, Mohammed Kareem; salim, Amjad jadir; Fingan, Esraa Sattar; farhan, Hawraa radad; Yousif, Hakam Basil (American Journal of Botany and Bioengineering, 2025)
Nanotechnology has become a frontier of science impacting several domains, co-existing across physical, chemical, biological, and engineering systems. This multidisciplinary feature has witnessed a growing interest in dimensions below micron to manipulate the properties of materials. The scale length of solid-state devices has been reduced to nanometer dimensions. Therefore, developments in instrumentation and process technologies are based on nanoscopic sciences, adding a new dimension to the design and analyze process of these electronic systems. Nanotechnology materials and structures are redefining the standard set of tools for analysis, which is becoming increasingly necessary to consider the dynamics of these structures. The control of these devices is not trivial; several effects such as the electronic obstacle position play an important role. The advent of new processes and techniques has also allowed the development of new materials with enhanced properties, which have had a central role in the miniaturization process and the increase of the density of electronic systems. Furthermore, for the first time, direct observation of movement of electrons within single atoms has been achieved. Nanoelectronics is considered disruptive and is predicted to have applications by 2025. There is, however, a balance of challenges to overcome: nanotechnology is facing a lack of understanding the new physical phenomena; scalability is still a fundamental issue for the new technologies to be widely adopted. Asia is considered leading in nanoelectronics research & development (R&D). In the future, the potential scope of research and development of nanotechnology and other science and engineering is important to cover. This encompasses the economic importance of applications, which includes microelectronics, traditional equipment industries, and new products and processes emerging from convergent technologies. It also includes the social, ethical, health, and environmental issues related to nanotechnology, and the public perception and acceptance challenge for developed countries.